Mathematical model for energy savings in blood donations at the Cienfuegos Blood Bank - David Lorenzo Calles; Manuel E. Cortés Cortés (Medisur)
Foundation: the electricity consumption of the Cienfuegos Blood Bank is governed by MINSAP Resolution 299, which regulates electricity consumption at the national level for blood banks. This consumption is 7.56 kW per donation. It is extremely important to determine the number of blood donors who minimize electricity consumption, and statistical-mathematical methods are used to do so. Objective: to develop a statistical-mathematical model to determine the number of blood donors who minimize electricity consumption at the Cienfuegos Blood Bank and comply with the institution's plans. Methods: statistical-mathematical tools were used to determine the minimum number of donations to be made at the Cienfuegos Blood Bank to reduce electricity consumption. A mathematical model was built using non-linear regression and the calculation of the Least Squares method, using MatLab and the application of Javascript software, which models the blood donation process and electrical consumption, determining the necessary number of daily donations to minimize electrical consumption. A database from the five-year period (2007-2021) of the Blood Bank's work was used. A proposal for daily donations is provided and compared with the current performance data of the Blood Bank. Results: Electrical consumption does not show statistically significant changes when the number of donations is greater than 1200 per month. However, the class composed of the number of donations: "less than 1200" shows a significantly lower monthly current consumption when the number of donations does not reach 1200. A statistical-mathematical model is obtained to analyze the problem and obtain the range of donations with the lowest energy consumption. Javascript software was created to solve the problem. Different scenarios were generated to observe their behavior, the modeling was divided into different numbers of daily donations, during the period of 5 years, 25, 30, 35, and 40 donations per day and the results that minimize energy consumption are given. Conclusions: the polynomial adjustment model for donations-electrical consumption and the specific software in Javascript that models the donation process, in the period studied, was useful to obtain the adequate number of daily donations and their electrical consumption, thus optimizing the process.